Gaya perbualan dalam teks kreatif bahasa Melayu (Jurnal Bahasa, 2022)
Grice (1975) proposed a conversation principle, that is Cooperative Principle (CP) in order to make one conversation coherent and effective. This principle is produced as maxim, i.e. quantity, quality, relation and manner. The basis of this principle is "say what you mean and mean what you say". However in a real conversation, the CP is not rigid - it can he flouted - as a speaker unintentionally would flout the maxim for certain reasons. This article, thus, is an attempt to analyze the style of a conversation in a Malay creative text, with the application of CP. Samples of discussions are taken from "Sungai Mengalir Lesu" (1997) written by A. Samad Said. This article aims to show the type of utterances in the text, and its implications to the listener The analysis of CP will he linked with the concept of speech acts. In other words, the analysis is a combination of CP and speech actions. This study hopes to highlight the Malay conversation style in a Malay creative text.